2021
DOI: 10.3390/su13073750
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Combined Application of Potassium Silicate and Salicylic Acid on the Defense Response of Hydroponically Grown Tomato Plants to Ralstonia solanacearum Infection

Abstract: Bacterial wilt, caused by soilborne pathogenic bacterium Ralstonia solanacearum, is a serious and widespread disease that affects global tomato production. Both silicon (Si) and salicylic acid (SA) play important roles in enhancing tomato resistance against bacterial wilt, however, their combined effects on the defense responses of infected tomato plants remain unknown. Hence, the combined effects of Si and SA on physiological and biochemical parameters of R. solanacearum-infected tomato plants were investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 105 publications
0
4
0
Order By: Relevance
“…On the other hand, MeJA application significantly increased ET and NEACs biosynthesis in a dose-dependent manner when it was applied against microorganisms in tomato seeds and plants [144]. Interestingly, ERFs genes (ERF1, ERF5, and ERF.C4), well-known as stress response factors associated with ET signaling, were upregulated by SA, MeJA, and ABA [80,82,90,124]. In tomato fruit, exogenous application of hormones (MeJA, BRs, and ABA) showed a positive effect on ET during the tomato fruit ripening [12,44,186].…”
Section: Crosstalk Among Hormones Against Oxidative Damage Caused By ...mentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, MeJA application significantly increased ET and NEACs biosynthesis in a dose-dependent manner when it was applied against microorganisms in tomato seeds and plants [144]. Interestingly, ERFs genes (ERF1, ERF5, and ERF.C4), well-known as stress response factors associated with ET signaling, were upregulated by SA, MeJA, and ABA [80,82,90,124]. In tomato fruit, exogenous application of hormones (MeJA, BRs, and ABA) showed a positive effect on ET during the tomato fruit ripening [12,44,186].…”
Section: Crosstalk Among Hormones Against Oxidative Damage Caused By ...mentioning
confidence: 99%
“…Moreover, some studies have indicated that, 24 h after SA application (0.2 and 1.0 mM), an increase in oxidative parameters is observed, which may trigger SAR [115,116]. For instance, SA application induces SAR in tomato plants against Alternaria solani [117,118], Fusarium oxysporum [119][120][121], Xanthomonas vesicatoria [122], Potato virus X [103], Tomato yellow leaf curl virus, Orobanche [123], Ralstonia solanacearum [124], Tomato mottle mosaic virus [125], and nematodes [126].…”
Section: Salicylic Acid (Sa)mentioning
confidence: 99%
See 1 more Smart Citation
“…Other researchers have also reported positive effects on plant growth with the application of SA and other compounds, such as potassium silicate (silicon), melatonin (MT) or the disaccharide trehalose in plants subjected to different types of stress. In the first case, silicon and SA were observed to play an important role in tomato plants in their resistance to the pathogenic effects of the Gram negative bacterium Ralstonia solanacearum [ 61 ], while the co-application of MT and SA improved growth in wheat plants subjected to salt stress. The co-application of MT and SA markedly improved plant functions such as the photosynthetic pigments content, photochemical reactions of photosynthesis, net photosynthetic rate, transpiration rate, stomatal conductance, as well as the osmoprotectants accumulation [ 62 ].…”
Section: Salicylic Acidmentioning
confidence: 99%